"She Blinded Me with Science": The Use of Science Frames in Abortion Litigation before the Supreme Court. (12th August 2022) - Moyer, Laura P.
Abstract: While much of the work on amicus briefs focuses on whether such briefs affect Supreme Court outcomes or doctrine, much less is known about the content of these briefs, particularly how groups opt to frame issues as part of their litigation strategy. In this study, I leverage an approach to content analysis that has previously been used to analyze judicial opinions and use it to assess the frames used by amicus groups in a single policy area over four decades. Using an original dataset of amicus briefs filed in Supreme Court cases on the right to abortion, I test the claim from the social movement literature that antiabortion groups have adopted the language of science in the post- Roe era. However, I find only limited support for such a shift, suggesting that litigation strategies may not track framing approaches used in other venues. Among antiabortion amici, only health organizations rely upon science framing, partially neutralizing the monopoly that prochoice health organizations had established with respect to scientific claims. By comparison, prochoice groups generally employ more science framing in their briefs than prolife groups and show evidence of calibrating this frame in response to changes in doctrine and court composition. Beyond its contributions to illuminating the movement-countermovement dynamics in abortion litigation, this study offers an approach that could be easily adapted to the study of other policy areas, contributes to the literature on social movements and framing, and advances our understanding of how organized interests assert themselves through the amicus curiae brief.